Virus mediated trophic interactions between aphids and their natural enemies. Issue 2 (26th November 2019) - Dupont, Corentin; Michiels, Alexandra; Sochard, Corentin; Dardenne, Nathalie; Meyer, Sophie; Brault, Véronique; Outreman, Yannick; Sentis, Arnaud
Abstract : Microbial endosymbionts alter the phenotype of their host which may have cascading effects at both population and community levels. However, we currently lack information on whether the effects of viruses on both host phenotypic traits and host population demography can modify interactions with upper trophic levels. To fill this gap, we investigated whether a prevalent densovirus infecting the aphid Myzus persicae (i.e. MpDNV) can modify trophic interactions between host aphids and their natural enemies (i.e. predators and parasitoids) by influencing aphid phenotypic traits (i.e. body mass and defensive behaviours), population demography (i.e. density and age‐structure) and susceptibility towards both predation and parasitism. We found that the virus decreased aphid body mass but did not influence their behavioural defences. At the population level, the virus had a minor effect on aphid adult mortality whereas it strongly reduced the density of nymphs and influenced the stage structure of aphid populations. In addition, the virus enhanced the susceptibility of aphids to parasitism regardless of the parasitoid species. Predation rate on adult aphids was not influenced by the virus but ladybeetle predators strongly decreased the number of aphid nymphs, especially for uninfected ones compared to infected ones. As a result, the virus decreased predator effect on aphid populations. By reducing both aphid quality and availability, increasing their susceptibility to parasitism, and modulating predator effect on aphid populations, we highlighted that viral endosymbionts can be prevalent drivers of their host ecology as they modify their phenotypes and interspecific interactions. These virus‐mediated ecological effects may have consequences on enemies foraging strategies as well as trophic webs dynamics and structure.